Mapping Evolving Internal Roles of the Armed Forces - Schnabel, Albrecht (SSR Papers, 2012)
It is widely assumed, at least from a Western perspective, that the armed forces provide national defence against external threats. In reality, within many consolidated Western democracies the armed forces are assuming an increasingly wide range of internal roles and tasks. These can include domestic security roles and the provision of humanitarian assistance in situations of natural or humanitarian catastrophe, often under the command and control of different civilian agencies. This SSR Paper seeks to make sense of this complex reality. Different internal roles of armed forces are analysed, drawing on the cases of Austria, Belgium, Canada, Denmark, Finland, France, Germany, Italy, Luxembourg, Netherlands, Norway, Spain, Sweden, the United Kingdom and the United States of America. Through carefully examining evolving internal roles and identifying patterns and lessons from these experiences, this SSR Paper provides an important contribution to understanding the evolving nature of contemporary armed forces.